2015
DOI: 10.1186/s40345-015-0025-1
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Finnish version of the Functioning Assessment Short Test (FAST) in bipolar disorder

Abstract: BackgroundThe Functioning Assessment Short Test (FAST) was developed for the clinical evaluation of functional impairment of patients suffering from bipolar disorder. The aim of this study was to validate the Finnish version of FAST.MethodsTranslation and back-translation of FAST were performed. Fifty patients with the Diagnostic and Statistical Manual of Mental Disorders-Fourth edition (DSM-IV) bipolar type I and II were interviewed at the Bipolar Disorder Research and Treatment Centre, City of Helsinki, Finl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
(27 reference statements)
0
6
0
3
Order By: Relevance
“…Hereby the domain of occupational functioning was altered slightly and items on the original FAST were translated to Dutch. The FAST has been validated in several languages for adult patients with BD and these studies all show similar positive results regarding its reliability and validity (Barbato et al 2013 ; Suominen et al 2015 ; Zhang et al 2018 ). However, to date the FAST has not been validated in an OABD sample.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Hereby the domain of occupational functioning was altered slightly and items on the original FAST were translated to Dutch. The FAST has been validated in several languages for adult patients with BD and these studies all show similar positive results regarding its reliability and validity (Barbato et al 2013 ; Suominen et al 2015 ; Zhang et al 2018 ). However, to date the FAST has not been validated in an OABD sample.…”
Section: Introductionmentioning
confidence: 77%
“…Given the lack of short, practical instruments to assess daily functioning in OABD, we altered the original FAST with regard to the area of work for the use in an older patient population. The original FAST (Rosa et al 2007 ) was already well-studied in several languages (Suominen et al 2015 ; Zhang et al 2018 ; Moro et al 2012 ; Cacilhas et al 2009 ; Aydemir and Burak 2012 ) and studies investigating psychometric qualities when used in the adult population showed positive results. In previous studies, the correlation between the FAST and the SOFAS scale was studied to assess the concurrent validity indicating a good concurrent validity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the SDS is a well-validated measure of disability and functional impairment in patients with bipolar and other psychiatric disorders (Leon et al, 1997;Arbuckle et al, 2009), it does not assess functional capacity in the same objective and comprehensive manner as more recently developed measures of functional impairment such as the Functioning Assessment Short Test (FAST) (Rosa et al, 2007) or the University of California at San Diego Performance-Based Skills Assessment (UPSA) (Mausbach et al, 2010). However, SDS total score was highly significantly correlated with FAST, total score (correlation r 40.74), and SDS work domain score correlated significantly with FAST occupational functioning (r ¼0.74) in patients with bipolar disorder (Suominen et al, 2015). Another limitation derives from the lack of inclusion of a measure of neurocognitive performance in the parent studies.…”
Section: Limitationsmentioning
confidence: 95%
“…A FAST é uma entrevista estruturada e breve que aborda seis domínios de forma independente: autonomia, funcionamento ocupacional, funcionamento cognitivo, relacionamento interpessoal e tempo livre. A escala foi validada para diversas populações (Suominen et al 2015, Barbato et al 2013) incluindo a brasileira (Cacilhas et al 2009). Os escores da FAST já foram correlacionados com os mais variados desfechos, desde estigma (Vázquez et al 2011), impulsividade (Jiménez et al 2012) e abuso de substâncias .…”
Section: Recuperação Clinica E Prejuízos Funcionais No Tbunclassified